1998
DOI: 10.1038/1418
|View full text |Cite
|
Sign up to set email alerts
|

Obligatory steps in protein folding and the conformational diversity of the transition state

Abstract: We have analyzed the existence of obligatory steps in the folding reaction of the alpha-spectrin SH3 domain by mutating Asp 48 (D48G), which is at position i+3 of an isolated two-residue type II' beta-turn. Calorimetry and X-ray analysis show an entropic stabilizing effect resulting from local changes at the dihedral angles of the beta-turn. Kinetic analysis of D48G shows that this beta-turn is fully formed in the transition state, while there is no evidence of its formation in an isolated fragment. Introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
241
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(261 citation statements)
references
References 54 publications
20
241
0
Order By: Relevance
“…A description of each of these intermediates was obtained by collecting characteristic structures from the simulation data. Most importantly, the structures that are produced share many features with those generated on the basis of experiment (21)(22)(23)(24)(25)(26). The present study demonstrates the utility of supplementing experiment with simulation and illustrates the important role that simplified protein models can play in increasing our understanding of protein folding.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…A description of each of these intermediates was obtained by collecting characteristic structures from the simulation data. Most importantly, the structures that are produced share many features with those generated on the basis of experiment (21)(22)(23)(24)(25)(26). The present study demonstrates the utility of supplementing experiment with simulation and illustrates the important role that simplified protein models can play in increasing our understanding of protein folding.…”
mentioning
confidence: 70%
“…Residues in the distal ␤-hairpin are also highly structured in the transition state for the ␣-spectrin SH3 domain (24). Another study concluded that formation of the distal loop in ␣-spectrin SH3 in an obligatory step in forming the transition state, because it is necessary to bring together strands ␤3 and ␤4 (25). With the exception of certain transition-state features that are not conserved among these homologous proteins [i.e., structuring of the C-terminal residues in the RT loop in src SH3 (23) and of the 3 10 helix in ␣-spectrin SH3 (24)], a strong correlation is observed between experiment and our simulation results.…”
Section: )mentioning
confidence: 99%
“…4 a and b emphasize the successive structures before entering͞escaping the ␣-helical basin. These two trajectories show that there are several, perhaps many, pathways for these reactions, and that this system has a transition region with more than one transition state, rather than a single transition state, as classical chemical kinetics would suggest (35,40). The two trajectories are presented here as an indication of the effect of entropy on the folding and unfolding processes.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the transition time of the unfolding reaction, ␣3␤, was defined as the time required to unwind the helix and to obtain a structure with 0% ␣-helical content and 83% ␤-sheet. The ␣-helical and ␤-sheet contents of any conformation of the conformation samples and of the folding͞unfolding trajectories were calculated by using the DSSP program (35). In addition, to estimate the effect of solvation on the stability of the two states of Ala 12 in vacuum, we collected 200 ␣-helical conformations and 200 ␤-hairpin conformations of Ala 12 , each sampled along 0.4-ns trajectories at 300 K by using vacuum, the EEF1 implicit solvation model, and the TIP3P explicit water models (36).…”
Section: Methodsmentioning
confidence: 99%
“…However, in protein folding studies, interpretational issues arise because most values are fractional, generally lying in the range of 0.1-0.5 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). These intermediate values might be due to partial structure formation in the TS or the presence of multiple TS structures.…”
mentioning
confidence: 99%